Harga Pokok Produksi dalam Kaitannya dengan Penentuan Harga Jual untuk Pencapaian Target Laba Analisis (Studi Kasus pada PT. Indra Brothers di Bandar Lampung) - Chairul Anwar; Lidia Fasi Ashari; Indrayenti INDRAYENTI (Universitas Bandar Lampung (UBL), 2010)
The purpose of this study was to determine the cost of production calculation is applied to the PT. Brother's senses and its effect on the determination of the selling price of the company, and the study is expected to be useful as a conceptual contribution to the company in conducting its business activities and for determining policies for the betterment of the company, particularly regarding the determination and the determination of cost of production in relation to the determination of the selling price.Based on the above problems posed hypothesis, namely: